An enzootic outbreak of acute disease associated with pathogenic E. coli in Adler monkey colony. Issue 6 (27th July 2015) - Lapin, Boris A.; Yakovleva, Lelita A.; Dzhikidze, Eteri K.; Gvozdik, Tatiana E.; Agumava, Aslan A.; Stasilevich, Zinaida K.; Danilova, Irina G.
Abstract: Background: In spring 2009 in Adler colony of the Institute of Medical Primatology, a large enzootic outbreak of acute intestine infection associated with pathogenic E. coli occurred and caused 5% mortality of population (209 animals). Methods: The epidemiological analysis, bacteriological investigation, postmortem examination, histological analysis, and PCR were used to identify the infectious agent. Results: Marked hemorrhagic diathesis, lethargy, dehydration, diarrhea with blood, wasting, and sometimes dystrophic changes in articular cartilages were noted. Morphologically, hemorrhagic enterocolitis and massive hemorrhages were found. PCR investigation of bacteriologically isolated E. coli characterized it as enteropathogenic and enteroinvasive E. coli . Conclusions: The outbreak in Adler colony slightly differed from similar outbreak in Florida in 2014 by more marked hemorrhagic diathesis and articular changes in some monkeys caused by polyavitaminosis developed in the course of infection. Sensitive to infection were M. mulatta, M. fascicularis, Cercopithecus aethiops, P. hamadryas and anubis, and Cebus capucinus .